Predicting the two predominant flexural failure paths of longitudinally reinforced high-performance fiber-reinforced cementitious composite structural members. (15th November 2019) - Shao, Yi; Billington, Sarah L.
Highlights: Two failure paths identified: failure after crack localization or after gradual strain hardening. An experimental demonstration illustrates the different mechanism of two flexural failure paths. Experiment shows a higher crushing strain for ECC due to its high spalling-resistance. A failure path prediction method and a minimum reinforcement area are proposed. A flexural strength prediction method is proposed for the two failure paths with an error within 13%. Abstract: High performance fiber-reinforced cementitious composite (HPFRCC) materials show higher tensile and compressive ductility than conventional concrete. When HPFRCC is used in place of traditional concrete for reinforced structural members (i.e., reinforced HPFRCC), the unique behavior of HPFRCC leads to different failure paths and modes than traditional reinforced concrete. As a result, the mechanics of failure of reinforced concrete members does not apply to the failure of reinforced HPFRCC flexural members. For structural design, it is necessary to understand the flexural failure paths and adopt appropriate prediction methods for reinforced HPFRCC members. In this study, two failure paths are identified through literature review and experimental demonstration: failure after crack localization and failure after gradual strain hardening. These two failure paths show distinct mechanical behavior and different ductility ranges. To mitigate the possibility of low ductility, a flexural failure path prediction method and a minimum reinforcing ratio equation are proposed for reinforced HPFRCC flexural members. A method to predict flexural strength based on a predicted failure path is developed and verified on 37 test results. Through a sensitivity analysis of the model parameters, the proposed method is shown to predict the strength of the collected test results with an error less than 13%.